Mavacamten, uma nova terapia revolucionária na HOCM: uma revisão de literatura - Tiago Filipe Sá Lopes Ribeiro Aguiar (2021)
Hypertrophic cardiomyopathy (HCM) is one of the most common inherited cardiac diseases, defined as a left ventricular wall thickness of ≥15 mm, in the absence of other causes of abnormal ventricular loading. A major hallmark of this disease is the presence of left ventricular outflow tract obstruction, which develops in up to ¾ of the patients, referred to as obstructive hypertrophic cardiomyopathy. Current treatment is offered to symptomatic patients, based on the presence of documented left ventricular obstruction, aimed at reducing symptoms and disease progression. This is achieved through pharmacological empirical therapy, surgery, alcohol ablation and/or pacing. Mavacamten is a first-in-class allosteric inhibitor of cardiac myosin that promises to provide clinicians with targeted therapy for these patients. The aim of this review is to provide a general overview of the modern approach in diagnosis and management of HCM, as well as to integrate all the current knowledge on Mavacamten, anticipating a future change in the treatment algorithm of patients with HCM.